Priority populations' experiences of the accessibility and inclusion of recreation centres: a qualitative study - Elise Rivera; Cynthia Smith; Kylie D Hesketh (BMC, 2024)
Abstract Background Although the health benefits of physical activity are well documented, certain priority populations are often disproportionately insufficiently active and at higher risk of poor health. Recreation centres have the potential to provide accessible and supportive environments for physical activity for all. However, little is known about priority populations' experiences of these venues and their views of how accessibility and inclusion can be optimised. This study aimed to gain in-depth insights of recreation centre experiences and potential strategies for improving inclusion and accessibility amongst priority populations (women, older adults, ethnic minorities, persons living with disabilities/additional needs, individuals identifying as LGBTQIA+, low socio-economic position). Methods This qualitative study (2021-2022) involved 18 semi-structured individual interviews with adult priority population users of recreation centres (50% 65 + years, 61.2% female) in one Melbourne municipality. Participants were asked to discuss their positive and negative experiences at the centres and to identify strategies for enhancing accessibility and inclusion. Interviews were audio-recorded and transcribed verbatim. Content analysis was performed for data analysis. Results While many participants had positive views of the facilities and programs at the centres, as they met their needs, they also had suggestions for improving accessibility and inclusion. Similarly, most participants were happy with the communications, felt included, and perceived the culture positively. Those who did not feel included at the centres offered many potential strategies for changing the culture, modifying communications (e.g., signage), and establishing partnerships for better access and inclusion. Conclusions The present study adds to essential knowledge concerning priority populations' experiences of recreation centres. For recreation facilities that were generally perceived as having positive inclusion and accessibility, the findings nonetheless highlighted suggestions for further enhancement. These strategies may be useful more broadly for improving accessibility and inclusion, thereby promoting physical activity and ultimately health for all.